Comparative education in Spain in the 21st century. Issue 4 (2nd October 2018) - García Garrido, José Luis; García Ruiz, María José
ABSTRACT: The current process of globalisation has led to a convergence of international and Spanish concerns regarding teaching and research issues in the area of comparative education. Both in their teaching and their research work, the academics within the Spanish comparative community display a notable – and typically Hispanic – heterogeneity. This includes their use of epistemologically diverse frameworks and paradigms as well as their penchant for intellectual and teaching traditions built upon a wide-ranging, diverse gnoseological foundation. Along with research agendas focused on topics well within the orthodoxy and tradition of the field, Spanish comparative work has also tackled subjects long advocated by the late-modern agenda such as post-colonialism, the world 'disorder' and refugees and hospitality pedagogy. The community's engagement with and analysis of the cultural reality of Latin America stands out as a specific feature of Spanish comparative studies. While the works published in the Revista Española de Educación Comparada ( REEC ) (Spanish Journal of Comparative Education) attest to the theorisation and markedly interdisciplinary nature of the analyses carried out by many of our academics, the authors of this essay argue for the inclusion of teleological perspectives. Only by incorporating the viewpoints offered by these teleological disciplines will we be able to stand up to the sterile, eminently relativist tendencies of post-modern epistemology.